Exploring wear at the nanoscale with circular mode atomic force microscopy - Noel, Olivier; Vencl, Aleksandar; Mazeran, Pierre-Emmanuel (Beilstein Journal of Nanotechnology, 2017)
The development of atomic force microscopy (AFM) has allowed wear mechanisms to be investigated at the nanometer scale by means of a single asperity contact generated by an AFM tip and an interacting surface. However, the low wear rate at the nanoscale and the thermal drift require fastidious quantitative measurements of the wear volume for determining wear laws. In this paper, we describe a new, effective, experimental methodology based on circular mode AFM, which generates high frequency, circular displacements of the contact. Under such conditions, the wear rate is significant and the drift of the piezoelectric actuator is limited. As a result, well-defined wear tracks are generated and an accurate computation of the wear volume is possible. Finally, we describe the advantages of this method and we report a relevant application example addressing a Cu/Al2O3 nanocomposite material used in industrial applications.
Keywords: circular mode atomic force microscopy; composite materials; image processing; nanowear; wear mechanisms